Social distancing without emotional distancing?1. (1st December 2021) - Hunt, Ava; Wooster, Roger
The COVID-19 pandemic has impacted every aspect of society and no more so than in educational applications of theatre for children in schools. This article explores the complexities of what applied theatre/drama offer the young to think critically and develop empathetic human relationships crucial to sound mental health. The article's authors reaffirm ways in which applied theatre/drama and TIE have contributed to healthy social development through contributions to the Personal, Social and Health Education curriculum. Cited are recent projects with compromised praxis in the face of the pandemic. Identified is a shift in educational priorities that are returning to traditional approaches in place of wider heuristic social education. Consequent moves to online teaching and imposition of social distancing has led to concerning levels of social distancing potentially impacting negatively on mental health of the young. However, applied theatre/drama disciplines play a particular role in facilitating emotional maturity through critical thinking.